2019
DOI: 10.3390/nu11092089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regular Kefir Consumption on Gut Microbiota in Patients with Metabolic Syndrome: A Parallel-Group, Randomized, Controlled Study

Abstract: Several health-promoting effects of kefir have been suggested, however, there is limited evidence for its potential effect on gut microbiota in metabolic syndrome This study aimed to investigate the effects of regular kefir consumption on gut microbiota composition, and their relation with the components of metabolic syndrome. In a parallel-group, randomized, controlled clinical trial setting, patients with metabolic syndrome were randomized to receive 180 mL/day kefir (n = 12) or unfermented milk (n = 10) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 80 publications
1
78
0
1
Order By: Relevance
“…It is a low-cost food, accessible to the general population, easy to handle and with great functional potential ( 18 ) due to its bioactive compounds ( 11 , 18 ) like exopolysaccharides, conjugated fatty acids and peptidases ( 11 , 16 ). Kefir consumption does not seem to result in negative effects ( 18 ) for adult humans ( 19 ) or animals ( 20 ). In kefir produced with whole milk, high cholesterol content can be observed, and in individuals with intolerance to lacteal proteins, allergic reactions may be observed, that can be avoided by replacing the milk matrices for water and sugar, which reinforces the absence of adverse effects of kefir ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is a low-cost food, accessible to the general population, easy to handle and with great functional potential ( 18 ) due to its bioactive compounds ( 11 , 18 ) like exopolysaccharides, conjugated fatty acids and peptidases ( 11 , 16 ). Kefir consumption does not seem to result in negative effects ( 18 ) for adult humans ( 19 ) or animals ( 20 ). In kefir produced with whole milk, high cholesterol content can be observed, and in individuals with intolerance to lacteal proteins, allergic reactions may be observed, that can be avoided by replacing the milk matrices for water and sugar, which reinforces the absence of adverse effects of kefir ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite not reaching statistical significance, several of the changes were correlated with improvements in anthropometric measurements. 14 …”
Section: Resultsmentioning
confidence: 99%
“…Vinderola et al (2006) proved that kefir activated immune system with down-regulation of Th2 response that promoted cell mediated immune response against tumor and pathogenic infection in mice. Previous studies performed by Bellikci-Koyu et al (2019) showed that consumption of kefir frequently for 12 weeks in patients having metabolic syndrome displayed microbiota alteration with the increase in Actinobacteria without any changes in Bacteroidetes and Proteobacteria population. Kefir possessed antioxidative, antibacterial and hepato-protective activity against CCl 4 induced liver toxicity in mice (AbdEl-Mogheith et al 2017).…”
Section: Kefirmentioning
confidence: 92%